Elements of Pregnancy and Parenthood Policies of Importance to Medical Students and Included in a Sample of Medical Schools' Websites and Student Handbooks - Jessica L.R. De Haan; Franklin Dexter; Bradley M. Fleming; Amy C.S. Pearson; Suzanne D. Reuter (Mary Ann Liebert, 2021)
Background: Medical students who are parents or considering parenthood often want information about school policies. An earlier survey of 194 medical students from one U.S. school examined seven ?elements that [students thought] should be included in a school policy on pregnancy/maternity leave.? For example, students want to know ?how much time a student can take off during medical school and still graduate with their class.? We performed multivariate and multivariable analyses of the University of South Dakota survey to understand its generalizability and usefulness. Methods: The earlier survey also included 35 demographic variables about individual students. We tested empirically for associations between the demographics and the seven policy items, thereby evaluating generalizability of the survey results to different demographic groups. We then surveyed public websites of a sample of U.S. medical schools to evaluate usefulness of the knowledge of the seven items. For the 33 surveyed schools, we documented if each of the items was present on publicly available webpages and handbooks. Results: The seven items had content validity as a necessary and sufficient set of items. There also were no significant associations of the items with demographic variables. Therefore, there is little chance that differences among medical schools in their average demographic would affect the items needed for their websites and student handbooks. Among the surveyed medical school websites, 1 of 33 had all seven items (upper 95% confidence limit: 14% of schools nationally would be expected to have all seven items shown). Conclusions: These findings show that it is known what information students want to know about in a school policy on pregnancy and parental leave. Adding these items to public websites is a necessary and an easily actionable intervention to help current and future medical students.